Norma Komunikasi Negosiasi dalam Tradisi Merariq: Analisis Etnografi Komunikasi Pada Masyarakat Sasak Desa Genggelang Lombok Utara - Tamrin, Andi (DAS Institute, 2023)
This study examines the patterns and norms of negotiation communication that occur in the merariq tradition in the Sasak community of Genggelang village, North Lombok. Merariq is a traditional wedding tradition with a series of complex communication stages, involving a negotiation process between the family of the prospective bride and groom mediated by a pembayun (traditional spokesperson). Using a communication ethnographic approach, this study aims to uncover and analyze in depth the communication components, interaction patterns, and norms that govern the negotiation process in the merariq tradition. The research method used is qualitative with an ethnographic approach of communication. Data collection was carried out through participant observations, in-depth interviews with the participants, traditional leaders, and families involved in the merariq process, as well as documentation of various stages of negotiations. The results of the study show that the communication norms in merariq negotiations have a hierarchical structure and are bound by strict customary rules. Pembayun as a mediator must master the base alus (subtle language) and understand the social stratification of the Genggelang community to be able to carry out their role effectively. The negotiation process includes the stages of selabar (notification), the discussion of ajikrama (traditional values), the determination of pisuke (a gift for the bride's family), and the determination of the time of the wedding procession. Each stage has specific verbal and non-verbal communication norms, including the use of figurative language, sitting positions, gestures, and proper timing in conveying messages. The study also revealed that the success of negotiations is highly dependent on the ability of the participants to manage intercultural communication, given the differences in social and economic backgrounds between the two families. The communication strategies used include a persuasive approach, the use of cultural symbols, and the application of consensus deliberation principles that are deeply rooted in the Sasak tradition. Other findings show a transformation in the practice of negotiation communication, where some aspects have been adapted to the modern context while still maintaining the core values of the tradition